Photoaffinity labelling of isopenicillin N synthetase. - Baldwin, J; Coates, J; Moloney, M; Pratt, A; Willis, A (1990)
The alpha-aminoadipoyl group of the natural substrate of isopenicillin N synthetase (IPNS), L-alpha-aminoadipoyl-L-cysteinyl-D-valine (ACV), has been replaced by a diazirinyl-containing group, which can be photoactivated. This has allowed investigation of the substrate binding site of IPNS by photoaffinity labelling. Laser flash photolysis of this analogue, [3H]DCV, in the presence of IPNS leads to the incorporation of radioactivity into the enzyme. Tryptic digestion of this labelled enzyme, followed by separation and sequencing of the resultant fragments, identified two labelled regions of the protein. These are the fragments Asp-40 to Arg-78 and Thr-237 to Gly-256.